Estrategia para la disminución de los costos de producción del cacao en el recinto Tinoco del cantón Baba, perteneciente a la provincia de Los Ríos - Gamboa Cedeño, Roberto Rafael (2018)
In the 1600 hundred, Ecuador started producing cocoa on their land, but it was until the year 1890, when the country started to export it worldwide. This cocoa had the international acceptance for its quality and fine aroma. This cocoa also called “cacao de arriba” or national. Nowadays are very few people that produce it, the reason is that it is very delicate in its care and because also in the ecuadorian market there is a seed that produces a type of cocoa that its more yield per hectaera, it is more resistant to pests and it is not as delicate as the cacao de arriba. This type of cocoa called CCN-51 or twig cocoa appeared during 1920, when cocoa pests and diseases develop such as the monilia, and the escoba de bruja, etc. The twig cocoa , is the favorite among farmers because of what it has been mentioned. On the other side the producers prefer this varierty because at the moment for selling the cocoa beans customers paid the same price for cacao de arriba or the twig cocoa. It is worth mentioning that oreign industries prefer the cacao de arriba for the elaboration of fine chocolate. But Ecuador is producing more CCN-51, and these companies end up mixing it with other varieties from other countries like Costa de Marfil, Ghana, Indonesia, among others………